РЕЛИГИОЗНОСТЬ И РЕЛИГИОЗНАЯ СОЦИАЛИЗАЦИЯ - Айрапетова, А.Г. (SCIENCE and SOCIETY, 2017)
The article deals with the study of young people's personal religiosity and religious socialization. Different authors' scientific approaches to the study of the religion, as a social aspect of religiosity, as well as the stages of its development were considered in the article. There is given the definition to the notion of religious socialization, six types of influences, which render the impact on the development of personal religiosity were demonstrated in the article.
Keywords: religion; dogmatic; confessional; religiosity; social-psychological features of personality; religious attitudes; religious socialization